Analysis of Creep in Functionally Graded Cylinder - Harmandeep (My University, 2010)
Creep is the tendency of a solid material to slowly move or deform permanently under the influence of stresses when subjected to high temperatures for long duration of time. So creep is one of the major considerations while analyzing the materials which are used for high temperature for long durations. Functionally Graded Materials (FGM) is the materials meant for high temperatures. FGM cylinders are used under high temperatures mainly in petroleum industry and nuclear power plants. So creep analysis of FGM cylinders has a wide scope for research. In this research work the radial and circumferential stress analysis of the FGM cylinders when subjected to internal and external pressures at high temperatures for long durations of time is done with the help of Ansys Software. The validation of the results is proved by matching the results with Jian Jun Chen et al. [16]. Further the effect of increasing internal pressure on the radial and circumferential stresses is seen. From the results obtained it is clear that they are in accordance with the results obtained by Jian Jun Chen et al. [16]. The results of the stress analysis showed that by increasing the internal pressure the radial and circumferential stresses increases directly proportional to internal pressure.
M.E. (CAD/CAM and Robotics)
Keywords: Creep, Norton Law, Radial Stress, Functionally Graded Material